Memaksimalkan Keuntungan UMKM Barry Furniture dengan Metode Program Linear Simpleks - Clara Rosita Hani Yuli Astuti; Rosa Angela Stefany; Wakhid Fitri Albar (Saintek Lahan Kering, 2023)
In today's era, furniture is a type of business that has big profits, however, it requires a large amount of capital to start the business. Many furniture entrepreneurs are competing to be the best by improving the quality of their products in order to obtain results that are worthy of competing with other products. In addition to quality, entrepreneurs also need to improve performance in order to achieve effectiveness and efficiency in running their business. This performance improvement aims to obtain the maximum possible profit. Barry Furniture UMKM also wants to experience this. To obtain maximum profit, proper analysis is needed so that this analysis can help entrepreneurs to achieve effectiveness and efficiency in running a business. In conducting the analysis, the Linear Programming analysis tool with the Simplex Method was used. From the results of this study it can be concluded that in order to obtain maximum profit, Barry Furniture needs to produce 60 tables and 60 chairs. If Barry Furniture follows the results of this analysis, it is estimated that in less than one month they will earn a profit of IDR 1,800,000.00.